Second-hand smoke exposure in adolescents in Latin America and the Caribbean: a pooled analysisResearch in context - Antonio Bernabe-Ortiz; Rodrigo M. Carrillo-Larco (Elsevier, 2023)
Summary: Background: Second-hand smoke exposure is prevalent amongst adolescents, despite of being a preventable risk factor associated with unfavourable outcomes. The distribution of this risk factor varies by underlying determinants and public health officers need contemporary evidence to update policies. Using the most recent data available from adolescents in Latin America and the Caribbean (LAC), we described the prevalence of second-hand smoking. Methods: Pooled analysis of Global School-based Student Health (GSHS) surveys conducted from 2010 to 2018 was conducted. Two indicators were analysed based on information from the 7 days prior to the survey: a) any exposure to second-hand smoking (0 vs ≥1 days of exposure); and b) daily exposure (<7 vs 7 days). Prevalence estimates were carried out accounting for the complex survey design, and reported overall, by country, by sex, and by subregion. Findings: GSHS surveys were administered in 18 countries, yielding a total of 95,805 subjects. Pooled age-standardised prevalence of second-hand smoking was 60.9% (95% CI: 59.9%-62.0%) with no substantial differences between boys and girls. The age-standardised prevalence of any second-hand smoking varied from 40.2% in Anguilla to 68.2% in Jamaica, and the highest prevalence was in the Southern Latin America subregion (65.9%). Pooled age-standardised prevalence of daily second-hand smoking was 15.1% (95% CI: 14.2%-16.1%), and was higher in girls than boys (16.5% vs 13.7%; p < 0.001). The age-standardised prevalence of daily second-hand smoking ranged between 4.8% in Peru to 28.7% in Jamaica, and the highest age-standardised prevalence was in Southern Latin America (19.7%). Interpretation: The prevalence of any second-hand smoking is high among adolescents in LAC, though estimates changed substantially by country. While policies and interventions to reduce/stop smoking are implemented, attention should also be paid to avoid second-hand smoke exposure. Funding: Wellcome Trust International Training Fellowship (214185/Z/18/Z).